Sierra Productiva and Sierra Exportadora Two Roads to Combat Poverty - Podestá Cuadros, Sergio Fernando (2018)
Poverty in Peru, is a condition very hard to explain given the extension of the territory, and its diversity. The property of agricultural land in Peru had an important turn after the Agrarian Reform: It went from 20,000 states to 1’7500,000 small farms, which in many cases, couldn’t achieve profitable results in their production. With the implementation of low cost and high impact technology, Sierra Productiva is changing that. With the help of Sierra Productiva and Sierra y Selva Exportadora, small and middle agrarian producers have become competitive in the local and foreign market. These models – Sierra Productiva and Sierra y Selva Exportadora – are examples to be replicated to defeat poverty and give back hope to our farmers and agrarian producers.